Large gastric leiomyoma mimicking gastrointestinal stromal tumor in 53-year-old patient – a case report and review of literature - Stanek, Magdalena; Życiński, Przemysław; Książek, Mariusz; Gutkowski, Krzysztof (European Journal of Clinical and Experimental Medicine, 2015)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Gastric mesenchymal neoplasms are often detected accidentally during the endoscopic diagnostic of upper gastrointestinal tract. Most of them are clinically insignificant small, benign lesions. When they reach large sizes, detailed endoscopic, imaging and histopathological diagnostic is required. Despite the fact that stromal tumors predominate among gastric mesenchymal neoplasms, in differential diagnosis we should take into consideration also other neoplastic lesions, including leiomyoma. Appropriate differentiation is significant, because of different therapy and medical control. In the article we presented a case of large gastric leiomyoma mimicking gastrointestinal stromal tumor in 53-year-old patient. We indicated pivotal elements of diagnostic algorithm with particular emphasis on localization of lesion, endoscopic and radiological image and also histopathological and immunohistochemical examination. The analysis has been supported by synthetic review of the latest literature.